Kohesi Leksikal Pada Abstrak Skripsi Mahasiswa Angkatan 2021 Program Studi Pendidikan Bahasa dan Sastra Indonesia - Lazarus Watti; Semuel H. Nitbani; Narantoputrayadi Makan Malay (Jurnal Lazuardi, 2026)
This study aims to analyze the use of lexical cohesion in the abstracts of theses written by students majoring in Indonesian language and literature in the 2021 cohort. This study uses a qualitative descriptive method, and the data in this study were collected through reading, note-taking, categorization, conclusion, and data presentation techniques in coding cards. The theory used in this study is the theory of cohesion based on the perspectives of Halladay and Hasan. The results of the study show that the use of lexical cohesion, which consists of six categories, namely repetition, synonymy, antonymy, hyponymy, collocation, and equivalence, increases the coherence of the abstract through the connection between linguistic elements and clarifies the meaning strategically, as well as enriching the message or information concisely and clearly in the abstract.